Comparison of the effects of intravenous dexmedetomidine of different target-controlled infusion pharmacokinetic models for propofol (Marsh vs Schnider) during induction of anesthesia - Siang, Tan Hai (2017)
Background: Dexmedetomidine is selective alpha 2-agonist which is commonly used for sedation and potential to be used as co-induction drug. The aim of this study was to determine the effects of dexmedetomidine on induction using different target-controlled infusion (TCI) pharmacokinetic models of propofol. Methods: 64 patients, aged 18-60 year-old, classified under ASA I and II, who underwent elective surgery under general anaesthesia, were randomised into two groups; Group Marsh (n=32) and Group Schnider (n=32). All patients received 1 mcg/kg loading dose of intravenous (IV) dexmedetomidine over 10 minutes and followed with TCI remifentanil at 2 ng /ml. After effect-site concentration (Ce) of remifentanil achieved 2 ng/ml, TCI propofol induction was started. Group Marsh was started with Marsh model at target plasma concentration (Cpt) of 2 mcg/ml, whereas Schnider group was started with Schnider model at target effect concentration (Cet) of 2 mcg/ml. If induction was unsuccessful after 3 min, target concentration (Ct) was gradually increased to 0.5 mcg/ ml every 30 seconds until succesful induction. Ct requirement of propofol at successful induction, induction time, Ce of propofol at successful induction and serial of haemodynamic parameters were recorded for statistical analysisResults: Requirement of Ct of propofol for successful induction was significantly lower in Group Schnider than Group Marsh [3.48 (0.90) vs. 4.02 (0.67) g/ml; P = 0.01]. Mean induction time was also shorter in Group Schnider than Group Marsh [134.96 (50.91) vs. 161.59 (39.64); P = 0.02] seconds. There were no significant differences in Ce at successful induction and haemodynamic parameters between the two groups. Conclusions: Dexmedetomidine as co-induction with TCI remifentanil and TCI propofol reduced Ct requirement for induction and shorter induction time in Schnider model than Marsh model of TCI propofol. However, haemodynamic effects were stable in both groups.